The cholera toxin B subunit induces trained immunity in dendritic cells and promotes CD8 T cell antitumor immunity - Tepale-Segura, Araceli; Gajón, Julián A.; Muñoz-Cruz, Samira; Castro-Escamilla, Octavio; Bonifaz, Laura C. (Frontiers in Immunology, 2024)
Innate immune training is a metabolic, functional, and epigenetic long-term reprogramming of innate immune cells triggered by different stimuli. This imprinting also reaches hematopoietic precursors in the bone marrow to sustain a memory-like phenotype. Dendritic cells (DCs) can exhibit memory-like responses, enhanced upon subsequent exposure to a pathogen; however, whether this imprinting is lineage and stimulus-restricted is still being determined. In addition, the functional consequences of DC training on the adaptive and protective immune response against non-infectious diseases remain unresolved. Here, we describe that the nontoxic cholera B subunit (CTB) can induce trained immunity in murine DCs. CTB-trained dendritic cells exhibit increased expression of TNFa, and metabolic reprogramming indicated by lactate dehydrogenase (LDH) expression. Moreover, CTB training has an imprint on DC precursors, increasing the number and function of bone marrow-derived Dendritic Cells (BMDCs). We found that immune training by CTB stimulates the recruitment of DC precursors in vivo and DCs infiltration at the inoculation site and at draining Lymph Nodes (dLN). Interestingly, immune training induced by CTB promotes a highly co-stimulatory phenotype in tumor-infiltrating DCs (CD86 + ) and a heightened functionality of exhausted CD8 T cells (Ki67 + , GZMB + ), which were associated with a protective response against melanoma challenge in vivo. These results indicate that CTB can induce innate immune training on DCs, which turns into an efficient adaptive immune response in the melanoma model and might be a potential immunotherapeutic approach for tumor growth control.